Properties of compress stabilised interlocking block using laterite soil with different cement - aggregate ratio - Muhammad Zukarnain, Zainal (2014)
Interlocking block is one of method in Industrialized Building System (IBS) as classified by the Construction Industry Development Board Malaysia (CIDB). Compressed Earth Interlocking Block (CEIB) is one of the part of block system that will reduce the time and cost construction for housing because it do not required mortar in bricklaying work. The aim of this research is to determine the suitable curing method and the compressive strength of the laterite interlocking block using different ratio of cement content. The different ratios of cement were used in producing the interlocking block (1:5, 1:6, 1:7, 1:8 and 1:9). In this experimental, there are 4 different curing methods to be conducted. The result from the curing sets experimental shows that Set 3# which is dry in sun curing method that give the highest compressive strength value (7.01 MPa) for 7 days of curing. The curing method of Set 3# will be used in the different ratio of cement content experimental and different type of cement which is comparing between YTL cement and Lafarge cement. The result from the different ratio of cement content shows that interlocking block with ratio of 1:5 cement give highest compressive strength value which is 8.60 MPa meanwhile for interlocking block using Lafarge cement give value of 4.30 Mpa.